The Influence of Environmental Factors and Human Activities on Land Snail Diversity in the Sumber Brantas Arboretum and IPB Bogor Campus) - Nurhayati, Putri Afin; Astuti Latif; Hanny Ramadhanti; Syifa Maulidia; Besse Fatimah; Windra Priawandiputra (Jurnal Moluska Indonesia, 2025)
This study aims to analyze the composition of terrestrial gastropods in two arboreta with different environmental characteristics. Sampling was conducted purposively using hand sampling methods. Environmental factors such as elevation, temperature, and light intensity were measured at each sampling plot. Additionally, shell morphology of the collected gastropods was analyzed. The results revealed differences in gastropod composition between the two arboreta, with Sumber Brantas Arboretum exhibiting a higher Shannon diversity index (0.97) compared to IPB University Arboretum (0.73). Parmarion sp. was the only species found in both locations. These differences in gastropod composition are likely influenced by significant variations in elevation and land-use patterns between the arboreta. The findings highlight the important role of environmental factors and land use in shaping terrestrial gastropod diversity, which can serve as bioindicators of ecosystem quality.